-(3x-5)+x=-5x+1+x

Simple and best practice solution for -(3x-5)+x=-5x+1+x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(3x-5)+x=-5x+1+x equation:



-(3x-5)+x=-5x+1+x
We move all terms to the left:
-(3x-5)+x-(-5x+1+x)=0
We add all the numbers together, and all the variables
-(3x-5)+x-(-4x+1)=0
We add all the numbers together, and all the variables
x-(3x-5)-(-4x+1)=0
We get rid of parentheses
x-3x+4x+5-1=0
We add all the numbers together, and all the variables
2x+4=0
We move all terms containing x to the left, all other terms to the right
2x=-4
x=-4/2
x=-2

See similar equations:

| x^2-7x+11=5 | | X/3-x/4=7/2 | | 6n-12=-8+3n-8 | | 1+8b=-15+6b | | 6n-12=3n-16 | | 15x-13+7x+19=180 | | 15=6-2x | | 4(x+1)-2x=5x-8 | | -15×=84-8x | | 4(3x+2)-7=0 | | 5x+x=10+x | | (2x+3)(x)=280 | | 5x+x=10x | | 2(1/7x)+2x=160 | | 4x-6=94 | | 1/3x+7×=5 | | 2(y-4)=5y-11 | | -8x+2-5x=-20x-2+15 | | 16n^2+32n-180=0 | | 4x-6=44 | | 2x+20+72=180 | | 3^(7y)=4 | | 6a-1=11+4a | | (7x+32)=180 | | (3x+8)(x)=240 | | 6n^+3n-63=0 | | (2x−9)^2=8 | | 7u-3=116 | | 7x=x+39 | | 9b-9=-369 | | -4x+2-8x+3+15x=9 | | 360=5x-5+9x+12+15+15x-60 |

Equations solver categories